2018
DOI: 10.1039/c8nr03600d
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing charges accumulated in an electric double layer by three-dimensional open-loop electric potential microscopy

Abstract: Charges accumulated in an electric double layer (EDL) play key roles in various interfacial phenomena and electronic devices. However, direct imaging of their spatial distribution has been a great challenge, which has hindered our nano-level understanding of the mechanisms of such interfacial phenomena and functions. In this study, we present direct imaging of charges accumulated at an electrode-electrolyte interface using three-dimensional open-loop electric potential microscopy (3D-OL-EPM). Conventional OL-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…First, the core–shell structure generated an increased interface and a heterogeneous system, which can lead to the accumulation of virtual charges at junction interfaces and the induction of a strong polarization effect due to the different dielectric properties of CFs, Fe 3 O 4 NPs, and PPy. This phenomenon is known as interfacial polarization, which can improve the absorptive ability under an alternative electromagnetic field . As shown in Figure S7, CF 0.5 Fe 3 O 40.15 PPy 0.35 exhibited a higher impedance matching property than other prepared suprafibrillar composites, which benefited Fe 3 O 4 NPs and PPy to interact with more incident EMWs.…”
Section: Resultsmentioning
confidence: 96%
“…First, the core–shell structure generated an increased interface and a heterogeneous system, which can lead to the accumulation of virtual charges at junction interfaces and the induction of a strong polarization effect due to the different dielectric properties of CFs, Fe 3 O 4 NPs, and PPy. This phenomenon is known as interfacial polarization, which can improve the absorptive ability under an alternative electromagnetic field . As shown in Figure S7, CF 0.5 Fe 3 O 40.15 PPy 0.35 exhibited a higher impedance matching property than other prepared suprafibrillar composites, which benefited Fe 3 O 4 NPs and PPy to interact with more incident EMWs.…”
Section: Resultsmentioning
confidence: 96%
“…8 For instance, potential pulsing at scanning nanoelectrodes has been used to locally probe and image ion distributions in the electrical double layer (EDL) that forms in solution at the solid-liquid interface with an electrode substrate. 9,10 Analogously to local probing, potential pulses at scanning nano/micro-electrodes have been used for driving local reactions at a substrate. Conned electrochemical etching, also referred to as micro/nano machining, has demonstrated a feature size of $200 nm, 11 where the duration of the pulse has been shown to inuence the extent of the electrochemical etching through the distance-limited EDL charging.…”
Section: Introductionmentioning
confidence: 99%
“…Combining potential pulsing with nanoscale electrodes has become an exciting approach in recent years to study localized charging phenomena of the solid-liquid interface, which has shown great potential with regards to the understanding and control of charge dynamics at solidliquid interfaces 8 . For instance, potential pulsing at scanning nano-electrodes has been used to locally probe and image ion distributions in the electrical double layer (EDL) that forms in solution at the solid-liquid interface with an electrode substrate 9,10 .…”
Section: Introductionmentioning
confidence: 99%